2019
DOI: 10.1002/johc.12103
|View full text |Cite
|
Sign up to set email alerts
|

Using a Collaborative Model in Supervision With International Counseling Students

Abstract: This article addresses the supervisory needs of international counseling students and provides recommendations for supervision through a collaborative supervision model. Collaborative supervision promotes a sharing emphasis on the roles of language, conversation, self, and stories, whereby both supervisee and supervisor develop a relationship that invites jointly creating knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Through collaborative supervision, supervisors and supervisees can build new knowledge. Thus, it performs an effective supervision activity (da Silva Pinheiro et al, 2014; Lau et al, 2019; MacKay & Brown, 2013). This finding is also in line with the experiment result of Wiyono et al (2015) which showed that collaborative active supervision based on humanistic principles is very effective in increasing teacher professional competence.…”
Section: Discussionmentioning
confidence: 99%
“…Through collaborative supervision, supervisors and supervisees can build new knowledge. Thus, it performs an effective supervision activity (da Silva Pinheiro et al, 2014; Lau et al, 2019; MacKay & Brown, 2013). This finding is also in line with the experiment result of Wiyono et al (2015) which showed that collaborative active supervision based on humanistic principles is very effective in increasing teacher professional competence.…”
Section: Discussionmentioning
confidence: 99%
“…However, satisfaction with supervision can also be affected by other variables. Studies on the satisfaction of supervision of international students (Lau et al, 2019;Mori et al, 2009) and foreign-born therapists in the United States (Kissil et al, 2013;McKinley, 2019) represent multicultural aspects. Mori et al (2009), based on research, suggest when supervising international students, discussions on culture must take place.…”
Section: Supervision Satisfactionmentioning
confidence: 99%
“…For almost two decades, the counseling and counselor education literature has featured an increased attention to international counselors-in-training (CITs) as a group. For instance, the literature captures international CITs' outcomes spanning from academic and social needs (Behl et al, 2017), counseling self-efficacy (C. , practicum experience (Xiong et al, 2022), to supervision (e.g., Fan & Haskins, 2020;Jang et al, 2014;Lau et al, 2019;D. Li et al, 2018).…”
Section: International Counseling Doctoral Studentsmentioning
confidence: 99%